2022
DOI: 10.1111/nph.17994
|View full text |Cite
|
Sign up to set email alerts
|

Root metabolome of plant–arbuscular mycorrhizal symbiosis mirrors the mutualistic or parasitic mycorrhizal phenotype

Abstract: Summary The symbiosis of arbuscular mycorrhizal fungi (AMF) with plants, the most ancient and widespread association, exhibits phenotypes that range from mutualism to parasitism. However, we still lack an understanding of the cellular‐level mechanisms that differentiate and regulate these phenotypes. We assessed the modulation in growth parameters and root metabolome of two sorghum accessions inoculated with two AMF species (Rhizophagus irregularis, Gigaspora gigantea), alone and in a mixture under phosphoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 94 publications
0
31
1
Order By: Relevance
“…Thus, the plant-AMF interactions are always not positive, but range from positive to neutral and even negative (Pankova et al, 2018;Neuenkamp et al, 2019). For example, Kaur et al (2022) inoculated two sorghum accessions with two AMF species (Rhizophagus irregularis and Gigaspora gigantea) and observed both positive and negative effects. He then found that the positive outcome of R. irregularis was associated with a faciliatory root metabolome, while the higher relative abundance of sugars in the G. gigantea treatment may indicate a potential carbon drain and lead to negative effects.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the plant-AMF interactions are always not positive, but range from positive to neutral and even negative (Pankova et al, 2018;Neuenkamp et al, 2019). For example, Kaur et al (2022) inoculated two sorghum accessions with two AMF species (Rhizophagus irregularis and Gigaspora gigantea) and observed both positive and negative effects. He then found that the positive outcome of R. irregularis was associated with a faciliatory root metabolome, while the higher relative abundance of sugars in the G. gigantea treatment may indicate a potential carbon drain and lead to negative effects.…”
Section: Introductionmentioning
confidence: 99%
“…Soil AMFs are beneficial for the absorption of soil nutrients ( de Gruyter et al, 2022 ). The Glomeraceae showed the highest P uptake efficiency and antagonistic activities against plant pathogens ( Kaur et al, 2022 ). However, Gigasporaceae showed a negative impact on the plant growth potential ( Li et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…and antagonistic activities against plant pathogens (Kaur et al, 2022). However, Gigasporaceae showed a negative impact on the plant growth potential (Li et al, 2008).…”
Section: Figurementioning
confidence: 99%
“…Since ellagitannins have antimicrobial properties, their lower content indicates an adaptive response of fine roots to promote the ectomycorrhizal association. The chemical construct of fine roots can thus vary with the type and extent of mycorrhizal association (Xia et al 2021, Kaur et al 2022. Drought did not alter the content and composition of lignin while they varied across root orders.…”
mentioning
confidence: 93%